Nitrate Derived From Beetroot Juice Lowers Blood Pressure in Patients With Arterial Hypertension: A Systematic Review and Meta-Analysis - Benjamim, Cicero Jonas R.; Porto, Andrey Alves; Valenti, Vitor Engrácia; Sobrinho, Andressa Crystine da Silva; Garner, David M.; Gualano, Bruno; Bueno Júnior, Carlos Roberto (Frontiers in Nutrition, 2022)
Background: Although there are a considerable number of clinical studies with BRJ rich in NO3 and hypertension, it is difficult to indicate the real effects of NO3- from BRJ on the BP of hypertensive patients because there are still no estimates of the effects of NO3- derived from BRJ on the BP of hypertension patients. Objective: To clarify these effects we developed a systematic literature review with a meta-analysis of randomized clinical trials (RCTs). Design: The searches were accomplished through EMBASE, Cochrane Library, MEDLINE, CINAHL, Web of Science, and LILACS databases. Included were single or double-blinded RCTs; participants older than > 18 years old with hypertension (systolic BP (SBP) > 130mmHg and diastolic BP (DBP) > 80mmHg). NO3- BRJ was required to consume in a format that possibly blinded participants/researchers. These studies should report the SBP and DBP values (mmHg) measured before and after treatment. Risk of Bias tools and GRADE were enforced. Results: Seven studies were included (218 participants). BRJ intervention time ranged from 3 – 60 days with daily dosages of 70 – 250mL of BRJ. After the intervention with NO3- from BRJ, SBP underwent significant changes (p<0.001) of -4.95 (95%CI: -8.88; -1.01) (GRADE: ⨁⨁⨁◯ Moderate), but not for DBP (p = 0.06) -0.90mmHg (95%CI: -3.16; 1.36) (GRADE: ⨁⨁⨁◯ Moderate), compared to the control group. Conclusions: The NO3- derived from BRJ reduces SBP, but not DBP in patients with arterial hypertension.